PLASTIC BITUMEN MIX ROAD - MR. HIMANSHU HANURMESH RIVANKAR; SANGEETA RIVANKAR (International Journal of Innovations in Engineering Research and Technology, 2021)
Roads are the main system of transport which serves the house to house access to the people. The roads are given chief priority in the economy and the security of the country. The countries having no roads or fewer roads are still facing the problems.Dr. Ahmad Khan an owner of a plastic company first thought that his product is not only a boon to the world but a big curse also. He first carried out tests to practically use the plastic in the road construction. He developed a technology in which he successfully used the plastic bitumen mix in patching of pot holes in roads